Pemberian Insentif dan Motivasi serta Pengaruhnya terhadap Produktivitas Kerja dalam Perspektif Psikologi Islam - Peni Indrawati (FADZAT: Jurnal Ekonomi Syariah, 2021)
The purpose of this study was to examine and analyze the simultaneous, partial and dominant effect of the variable incentives and motivation on employee productivity. This research is explanatory (explaining) is "to test the hypotheses of a cause-and-effect relationship between the symptoms (variables) being studied. The type of data used is the type of quantitative data which is quantified using a Likert scale. The research population is employees of PT. Rijan Dinamis Selaras (RDS) Pacet Mojokerto. Data analysis used multiple linear regression. The results showed that: 1) incentives and motivation had a simultaneous effect on employee productivity. 2) the provision of incentives has no partial effect on employee work productivity and motivation has a partial effect on employee work productivity 3) motivation has a dominant effect on employee work productivity.